An Analysis of Islamic Education Financing Concepts through the Management of Business Incubation Assistance: A Case Study at an Islamic Boarding School - Mustaqim, Mustaqim; Karim, Hamdi Abdul; Indra, Yossefli (El-Rusyd, 2026)
This study aims to analyze the concept of Islamic education financing through the management of business incubation assistance at the Madinatul Munawwarah Islamic Boarding School. This study employs a qualitative approach using the case study method. Data collection was conducted through interviews with the foundation and business managers, as well as direct observation of the boarding school’s business activities. The results indicate that the management of business incubation assistance can serve as a productive alternative source of financing. The business units developed contribute approximately 5%–10% to the boarding school’s operational needs. These findings suggest that integrating Islamic education financing with entrepreneurship can strengthen the financial independence of Islamic educational institutions.